Puisi Sebagai Metode Alternatif dalam Pembelajaran Bahasa Inggris - Munjin Munjin (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2015)
There is still a notion stated by some students that English language is difficult and bored It is like a big monster which has always to be avoided, moreover it is to be one of the National Final Examination materials, English can make them upset dan frustrate. Why do the students sill have an opinion like this? The answer is that the teachers still use, in teaching English, traditional method and strategy which are unapropriate to the students’ demand. Poem as a material of teaching is, according to the writer, considered as a method which can increase students’ interest in studying English. Because the teaching will run in a joyful atmosphere, there is no burden on students’ shoulders